Liquid Metal-Embedded Layered-PDMS Antenna for Flexible and Conformal Applications - Wang, Meng; Liu, Zhifu; Dong, Jian (Frontiers in Physics, 2022)
This article proposes a dual-band slot IFA antenna using a combined technique of liquid metal (LM) filling and polydimethylsiloxane substrate. The antenna working at 2.4 and 5.8 GHz consists of three liquid metal layers—radiation patch, short circuit stub, and ground plane and can be bent to different radiuses for flexible, conformal, and wearable applications. The vacuum filling method enables realization of a monolithic-integrated substrate. The applicability of this antenna for a wearable wristband is validated through simulation.